1984
DOI: 10.1111/j.1365-2273.1984.tb01483.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective trial of unilateral grommets for bilateral secretory otitis media in children

Abstract: Fifty-four children with established chronic secretory otitis media, who had failed to respond to medical measures were treated with adenoidectomy and insertion of 1 grommet on a side chosen at random. Both sides improved and remained significantly improved at 12 months (P less than 0.001). At 3 months, the side with the grommet improved significantly more than the other side (P less than 0.05) but at 12 months there was no significant difference between the 2 sides (P greater than 0.1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…1,[11][12][13][14][15][16] Although comparisons are difficult due to differences in inclusion criteria, study periods and assessed outcomes, a recent Cochrane meta-analysis concluded that simple myringotomy appeared to offer no benefit, compared with no treatment. 5 Moreover, studies of the combined effect of adenoidectomy and tympanostomy tube insertion found an additional benefit of only 3-4 dB (95 per cent confidence interval 2-5 dB) at six months, compared with the ear without tympanostomy tube.…”
Section: Discussionmentioning
confidence: 99%
“…1,[11][12][13][14][15][16] Although comparisons are difficult due to differences in inclusion criteria, study periods and assessed outcomes, a recent Cochrane meta-analysis concluded that simple myringotomy appeared to offer no benefit, compared with no treatment. 5 Moreover, studies of the combined effect of adenoidectomy and tympanostomy tube insertion found an additional benefit of only 3-4 dB (95 per cent confidence interval 2-5 dB) at six months, compared with the ear without tympanostomy tube.…”
Section: Discussionmentioning
confidence: 99%
“…We first screened the articles by title/abstract and excluded five trials in which all children underwent adenoidectomy. [31][32][33][34][35] An additional 467 studies were excluded for other reasons, for example follow-up for <12 months. In total, 31 articles were eligible for further assessment.…”
Section: Searchesmentioning
confidence: 99%
“…Similarly, where grommets were inserted unilaterally for bilateral glue ear, little diVerence was found between the treated and the untreated ears at 12 months. 8 Further evidence is given in the bulletin to the eVect that any long term physical damage to the ear as a result of the presence of "glue" is negligible when compared with the risks associated with intervention. No benefits can be described to counter concerns that a policy of watchful waiting would produce unnecessary suVering for those children where the glue ear proved to be persistent and grommet insertion was finally recommended.…”
Section: Choice Of Individual Respondentsmentioning
confidence: 99%